Identification of Bacillus anthracis, Brucella spp., and Coxiella burnetii DNA signatures from bushmeat - Katani, R.; Schilling, M.A.; Lyimo, B.; Eblate, E.; Martin, A.; Tonui, Triza; Cattadori, I.M.; Francesconi, S.C.; Estes, A.B.; Rentsch, D.; Srinivasan, S.; Lyimo, S.; et al. (Springer, 2021)
Meat from wildlife species (bushmeat) represents a major source of dietary protein in low- and middle-income countries where humans and wildlife live in close proximity. Despite the occurrence of zoonotic pathogens in wildlife, their prevalence in bushmeat remains unknown. To assess the risk of exposure to major pathogens in bushmeat, a total of 3784 samples, both fresh and processed, were collected from three major regions in Tanzania during both rainy and dry seasons, and were screened by real-time PCR for the presence of DNA signatures of Bacillus anthracis (B. anthracis), Brucella spp. (Brucella) and Coxiella burnetii (Coxiella). The analysis identified DNA signatures of B. anthracis (0.48%), Brucella (0.9%), and Coxiella (0.66%) in a total of 77 samples. Highest prevalence rates of B. anthracis, Brucella, and Coxiella were observed in wildebeest (56%), dik-dik (50%), and impala (24%), respectively. Fresh samples, those collected during the rainy season, and samples from Selous or Serengeti had a greater relative risk of being positive. Microbiome characterization identified Firmicutes and Proteobacteria as the most abundant phyla. The results highlight and define potential risks of exposure to endemic wildlife diseases from bushmeat and the need for future investigations to address the public health and emerging infectious disease risks associated with bushmeat harvesting, trade, and consumption.